METAMORPHISM OF SULFIDES AND GANGUE QUARTZ AT THE DEGDEKAN AND GOL'TSOVSKY GOLD DEPOSITS, MAGADAN OBLAST - Voroshin S.V.; Tyukova E.E.; Gibsher N.A. (My University, 2006)
The Degdekan and Gol'tsovsky gold-quartz deposits are located in the southeastern Yana-Kolyma gold belt. The orebodies occur as quartz veins hosted in metaterrigenous rocks and cut by postmineral basic-intermediate dikes. It was established that metamorphism of sulfides and gangue quartz was restricted to a few centimeters off the dike contact. According to sulfide geothermometers, the metamorphic temperatures close to the contact of dikes attained 700°C at the Degdekan deposit and were no higher than 491°C at the Gol'tsovsky deposit. The formation of the forbidden assemblage of quartz and loellingite and its fine-grained texture indicate that the thermal effect on the Degdekan ore was short-term. The prolonged heating of the ore at the Gol'tsovsky deposit gave rise to the aggradation recrystallization of quartz and the formation of equilibrium sulfide aggregates that show only insignificant differences in composition from the primary phases. The average homogenization temperature of primary and pseudosecondary fluid inclusions is 206 ± 40°C in the unmetamorphosed veins and 257 ± 33°C in the metamorphosed veins. The salinity of fluids in the primary and pseudosecondary inclusions in quartz veins of both types varies from 0.5 to 14.0 wt % NaCl equiv. The melting temperature of liquid CO2 in the carbon dioxide inclusions, ranging from -57.0 to -60.8°C, suggests an admixture of CH4 and/or N2. The unmetamorphosed quartz veins were formed at a fluid pressure varying from 0.7 to 1.3 kbar, while quartz veins at the contact with dikes crystallized at a pressure of 0.8-1.5 kbar. The results of gas chromatography showed the presence of CO2 and H2O, as well as N2 and CH4. The average bulk of volatiles contained in the fluid inclusions in quartz from the metamorphosed veins is 1.5-2 times lower than in the unmetamorphosed veins; this proportion is consistent with the occurrence of decrepitated gas inclusions in the heated quartz. © Pleiades Publishing, Inc. 2006.